Editorial: The challenge of Economic, Statistical and Social Research at UNI - El Director (2018)
The National University of Engineering, through its Faculty of Economic Engineering, Statistics and Social Sciences, has assumed a special challenge in contributing proposals in the area of economic policies, the development of statistical models and the evaluation of Peru's social problems since the 1960s. The challenge of research in a public university is great, considering the scarcity of both physical and human resources. Nevertheless, the efforts made have been producing increasingly positive results, as evidenced by the scientific publications that have been appearing in recent years, including those of the Institute of Economic and Social Research of our Faculty.